Four new species of Desmopachria Babington from Peru (Coleoptera: Dytiscidae) - Miller, Kelly B. (Zootaxa, 2005)
Four new species in the genus Desmopachria Babington are described from Madre de Dios, Peru: D. pilosa Miller, n. sp. (D. convexa species group), D. balionota Miller, n. sp. (D. nitida species group), D. annae Miller, n. sp. (D. nitida species group), and D. tambopatensis Miller, n. sp. (ungrouped). Diagnostic characters, including habiti and male genitalia, are described and illustrated.